Evolution toward ovarian-sparing surgery in pediatric ovarian tumors: a 20-year single-center experience - Balcı, Özlem; Karaman, İbrahim; Yağız, Beytullah; Şahin, Gürses; Bolat, Özcan; Karaman, Ayşe (The Turkish Journal of Pediatrics, 2026)
Background. Ovarian tumors are rare in children, accounting for 1-2% of all pediatric malignancies. Recent trends emphasize fertility preservation, but data on the evolution of practice and outcomes remain limited. This study examines changes in surgical management and outcomes of pediatric ovarian tumors over two decades.Methods. All children who underwent surgery for ovarian pathologies at a tertiary pediatric surgery center between 2002 and 2021 were reviewed. Patients with histopathologically confirmed ovarian tumors were included. Clinical characteristics, surgical approaches, histopathology, and outcomes were analyzed. Patients were divided into two 10-year periods to evaluate trends over time, and age-based subgroup analysis compared prepubertal (≤12 years) and pubertal (>12 years) patients.Results. Of 324 children undergoing ovarian surgery, 87 had histologically confirmed tumors. The most common histological type was mature cystic teratoma (54.0%). Eighteen tumors (20.7%) were malignant. Ovarian-sparing surgery (OSS) increased from 20.0% (6/30) to 61.4% (35/57) (p
Keywords: ovarian tumor; pediatric; ovarian-sparing surgery; fertility preservation; oophorectomy; mature cystic teratoma